Hotspots of narrow endemisms: adequate focal points for conservation in Dendrochilum (Orchidaceae) - Pedersen, Henrik (2015)
The general aim of conservation is to ensure persi- stence of biodiversity value. Given certain measures (financial, logistic, etc.) the specific goal must be to maximize the amount of biodiversity value to be secured by these means. Several area selection met- hods are available for such purpose, and they repres- ent very different conservation philosophies (Williams et al. 1996; Humphries 2006). Two funda- mentally different approaches exist: (1) locating hot- spots of species richness or narrow endemism, and (2) designating conservation areas according to com- plementarity methods.